STATUS OF CHILDREN OUT OF MARRIED IN FIQIH PERSPECTIVE AND POSITIVE LAW IN INDONESIA - Annisa Fuji, Felly (USRAH: Jurnal Hukum Keluarga Islam, 2021)
Children are a gift from Allah SWT. that given to human. Grace that should be guarded, guided, loved and nurtured by faith and piety. In Indonesia, children are very much protected from their rights and positions. In Law Number 1 of 1974 concerning Marriage, the position of children consists of legitimate children and children outside of marriage. In Law No.1 of 1974 concerning Marriage, it is explained that a legitimate child is a child born in or as a result of a legal marriage (article 42 of Law No.1 of 1974). Meanwhile, children outside of marriage are regulated in article 43 of Law no. 1 of 1974 paragraph (1) Children born out of wedlock only have a civil relationship with their mother and their mother's family. Paragraph (2) The position of the child referred to in paragraph (1) above will further be regulated in a Government Regulation. The birth of a child outside of marriage is not only caused by a relationship outside of marriage, in certain circumstances it can also give birth to a child outside of marriage, such as a marriage that is carried out by custom or by religion only and is not registered in accordance with the laws and regulations in force in Indonesia